Judicial Decision-Making and the Realization of Justice in the Indonesian Criminal Law - Haryadi, Slamet; Ja’far, A. Kumedi; Dwiono, Sugeng; Fikma Edrisy, Ibrahim; Dwi Subarkah, Amirah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
The phrase